Hydrological and Morphological Changes of the Lower Danube Near Mohács, Hungary - Nagy, Judit; Kiss, Tímea (Journal of Environmental Geography, 2016)
Various direct human impacts changed the hydro-morphology of the Danube during the last centuries. The aims of the present study are (1) to analyze the water regime of the Danube River using the data of Mohács gauging station (1900-2013), and (2) to study the channel development (1952-2014) in connection with water regime changes and human impacts at a section near Bogyiszló (upstream of Mohács). According to the results the height of low water stages decreased by approx. 136 cm (1.2 cm/year), and new, high record flood stages were measured too. The discharge values appertaining to the same low water stages doubled, thus nowadays almost twice as much water flows through the cross-section of the channel at a given stage as at the beginning of the studied period. As the duration of low stages increased, the sandbar development intensified, thus the channel became narrower (by 48% at some places) and deeper thalweg evolved. Therefore, a smaller cross-section for flood-waves evolved, affecting the height of flood. These changes affect shipping, as due to riverbed incision and decrease of low water stages, the lowest shipping water level has to be set repeatedly at lower stages. Besides water extraction from the channel will have difficulties, thus irrigation and industrial cooling water supply will be limited in the future.